PENEGASAN EKSISTENSI KEPUTUSAN TATA USAHA NEGARA YANG TIDAK DAPAT DIJADIKAN OBJEK SENGKETA PADA PENGADILAN TATA USAHA NEGARA MELALUI PENGUNDANGAN UNDANG-UNDANG NOMOR 2 TAHUN 2020 - Indah Mutiara Sari; Anna Erliyana (Jurnal Hukum dan Bisnis (Selisik), 2022)
The promulgation of Article 27 paragraph (3) of Law Number 2 of 2020 adds to the precarious atmosphere of the pandemic that has occurred since 2020. The law that was present with the aim of providing procedures for implementing government actions in dealing with this pandemic turned out to have brought many questions from the general public regarding the interests of the general public. The political party that accompanies the promulgation of the law is because it is considered to provide immunity to state administrative officials against policies that will be issued as an effort to handle the COVID-19 pandemic because it is not an object of state administration. This research comes with several fundamental questions such as why the law legitimizes the existence of state administrative decisions that cannot be the object of a lawsuit at the state administrative court and how the general principles of good governance can be guaranteed to be implemented if the transformation of state administrative policies into the object of the state administrative dispute is removed. This research is based on normative juridical research methods